Profitabilitas dan Nilai Perusahaan: Peran Mediasi Kinerja Lingkungan - Amelia Natasya Sugiyanto; Natasia Alinsari (Postgraduate Program Merdeka University, 2022)
The value of the company is very important for the company because it can affect the views of stakeholders on the company's performance. Firm value is influenced by various factors, one of which is company profitability. Based on previous research, there are inconsistencies in research results, therefore researchers want to re-examine previous studies to see the effect of profitability on firm value with environmental performance as a moderating variable. In this study, companies engaged in the food and beverage industry were used that were listed on the Indonesia Stock Exchange in 2017-2020. The sample used consisted of 56 company data using purposive sampling technique. The results of this study indicate that profitability has a positive influence on firm value and environmental performance cannot moderate the relationship between profitability and the companyDOI:https://doi.org/10.26905/afr.v5i2.7542